Timing and risk factors associated with relapse among smokers attempting to quit in Malaysia - Yasin, S.M.; Moy, Foong Ming; Retneswari, M.; Isahak, M.; Koh, D. (2012)
BACKGROUND: Many smokers attempt to quit smoking, but very few succeed. OBJECTIVE: To identify the timing and risk factors involved in smoking relapse. METHODS: We conducted a prospective cohort study among staff in two public universities in Malaysia. Behavioural therapy with free nicotine replacement therapy was given as treatment. Participants were followed up for 6 months. Relapse was defined as returning to smoking after having quit for at least 24 h. RESULTS: Of 185 smokers who volunteered to participate, 120 achieved at least 24-h abstinence, and 80 of these relapsed within 2 months. Compared to participants who attended a single smoking cessation session, participants who attended three sessions had a lower likelihood of relapse within 6 months of quitting. In contrast, smokers with a much longer exposure to cigarette smoking in the workplace (>3 h per week) had a greater chance of relapse compared to those with no exposure. CONCLUSIONS: Frequent attendance at clinic sessions and less exposure to other people smoking in the workplace can potentially reduce the likelihood of relapse among smokers who have recently quit.